Digital Ethics and Spirituality in Islam - Kholil Syamsul; Moh. Affan; Muhammad Eko Arief Wijaksono; Zarkoni; Achmad Jasuli Afandi; Ahmad Syauqi Alaikar Rohman; Hasbullah (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
The rapid development of digital technology has significantly transformed social interaction patterns and religious practices among Muslims; however, these changes are not always accompanied by adequate ethical and spiritual awareness. This study aims to comprehensively analyze the integration of digital ethics and spirituality from an Islamic perspective, identify moral and spiritual challenges in digital spaces, and examine the role of Islamic education in fostering spiritually grounded digital ethical awareness. This research employs a qualitative approach based on a systematic literature review, utilizing data sources such as scholarly journal articles, academic books, conference proceedings, and relevant research reports published within the last five years. Data were analyzed through stages of literature reduction, thematic categorization, conceptual synthesis, and theoretical interpretation. The findings indicate that digital ethics in Islam is rooted in moral values such as ṣidq (truthfulness), amanah (trustworthiness), and ihsan (excellence), which must be integrated with spirituality as an internal mechanism for shaping moral consciousness. Major challenges in digital spaces include ethical degradation, spiritual distraction, and the influence of algorithms that shape religious practices in a non-reflective manner. Additionally, a gap exists between normative understanding and actual digital behavior. In this context, Islamic education plays a strategic role as a transformative agent through the internalization of moral values and the strengthening of spiritual dimensions. In conclusion, the integration of digital ethics and Islamic spirituality represents a holistic approach essential for building a digital society that is ethical, civilized, and oriented toward transcendental values.